2008
DOI: 10.1038/ng.202
|View full text |Cite
|
Sign up to set email alerts
|

Multiple polymorphisms in the TNFAIP3 region are independently associated with systemic lupus erythematosus

Abstract: The TNFAIP3 (tumor necrosis factor alpha–induced protein 3) gene encodes a ubiquitin editing enzyme, A20, that restricts NF-κB–dependent signaling and prevents inflammation. We show that three independent SNPs in the TNFAIP3 region (rs13192841, rs2230926 and rs6922466) are associated with systemic lupus erythematosus (SLE) among individuals of European ancestry. These findings provide critical links between A20 and the etiology of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
353
8
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(374 citation statements)
references
References 10 publications
11
353
8
2
Order By: Relevance
“…More recently, this gene region has also been associated with SLE in two independent studies. 21,22 In Musone et al 22 three independent associations conferring risk were associated with SLE, including the two SNPs previously associated with RA. However, Graham et al 21 found two independent associations, one of which was previously associated with RA.…”
Section: Stat3mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, this gene region has also been associated with SLE in two independent studies. 21,22 In Musone et al 22 three independent associations conferring risk were associated with SLE, including the two SNPs previously associated with RA. However, Graham et al 21 found two independent associations, one of which was previously associated with RA.…”
Section: Stat3mentioning
confidence: 99%
“…18 We selected single nucleotide polymorphisms (SNPs) for genotyping that had shown a convincing evidence of association with at least one other autoimmune disease from genome-wide association scans published over the past 2 years. We genotyped SNPs from the genes: CD58 (rs12044852) which has been associated with multiple sclerosis; 8 STAT3 (rs3816769) which has been associated with CD; 7 IL1A (rs17561) and ERAP1, previously called ARTS1 (rs30187) which have been associated with AS; 15,17 MMEL1-TNFRSF14 (rs3890745), CDK6 (rs42041), the 7q23 gene desert (rs11761231), CCL21 (rs2812378), TRAF1/C5 (rs3761847), KIF5A(rs1678542) and CD40 (rs4810485), which have been associated with RA; 7,12,19 BANK1 (rs10516487), FAM167A previously called C8orf13 (rs13277113) and ITGAM (rs9888739) which have been associated with SLE [9][10][11]20 and STAT4 (rs7574865) and TNFAIP3 (rs6920220 and rs10499194) which have been associated with both RA and SLE 13,14,16,21,22 (See Table 1 for full gene names).…”
mentioning
confidence: 99%
“…This includes TNFAIP3, where it appears that at least one component of the RA risk is different from the SLE risk haplotype. [17][18][19] The shared risk factors appear to have unique overlaps between different autoimmune diseases. For example, the PTPN22 Arg620Trp that is sheared between several autoimmune diseases including T1DM and RA has been shown not to be a risk factor in MS, whereas in the present studies CD226 and CLEC16A variations are shared risk factors between MS and T1DM.…”
mentioning
confidence: 99%
“…While only one missense coding allele has been identified thus far (in SLE), the wellestablished antiinflammatory functions of A20 in mice suggest that hypomorphic function or expression of A20 may contribute to the pathophysiology of these human conditions (24). Collectively, these findings suggest that subtle germline TNFAIP3 hypomorphisms may predispose individuals to chronic autoimmune diseases, whereas gross A20 deficiencies occurring somatically may contribute to lymphoma.…”
Section: A20 In Lymphocytesmentioning
confidence: 84%
“…(SLE), rheumatoid arthritis, psoriasis, and celiac disease (24)(25)(26)(27)(28)(29). While only one missense coding allele has been identified thus far (in SLE), the wellestablished antiinflammatory functions of A20 in mice suggest that hypomorphic function or expression of A20 may contribute to the pathophysiology of these human conditions (24).…”
Section: A20 In Lymphocytesmentioning
confidence: 99%